Karakterisasi dan Skrining Fitokimia dari Daun Violces (Viola odorata) - Surahmaida, Surahmaida; Mangkoedihardjo, Sarwoko (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Violces (Viola odorata) have been proven to have many pharmacological benefits as traditional medicine. Its leaves are traditionally used to treat headaches, coughs, colds, bronchitis, and asthma. This study aims to obtain scientific data on the pharmacognostic profile of fresh leaf and fine powder simplisia of violces, as well as to identify the secondary metabolite compounds of the methanol extract of violces leaves. The research method used is a pharmacognostic study (macroscopic, microscopic, and powder microscopy) and phytochemical screening using GCMS and analyzed descriptively qualitatively. Pharmacognostic observations on fresh leaf simplisia showed the presence of fibers, multicellular trichomes, spiral and ladder-type vascular bundles, stomata, covering hairs, and cork tissue. Fragments in the fine powder of violces leaves identified included fibers, multicellular trichomes, spiral and ladder-type vascular bundles, stomata, covering hairs, and stone cells. The results of GCMS analysis of the methanol extract of Violces leaves showed the presence of 27 identified chemical compounds It can be concluded that the pharmacognostic fragments and chemical compounds in this study will help in the identification and standardization of leaves from the Viola odorata species.